Identification of shared important genes associated with ferroptosis across different etiologies of acute lung injury - Jing Li; Yanming Yang; Zhengjun Cui (Scientific Reports)
Abstract Acute lung injury (ALI) of different etiologies has shared pathophysiologic process, from which we speculated that ALI of different etiologies may share common molecular features. While the shared genetic characteristics of ALI remain unclear. In this paper, we aimed to identify shared ferroptosis-associated and bottleneck genes from acute lung injury of different etiologies. Firstly, we extracted five groups of gene sets related to three distinct models of ALI from the Gene Expression Omnibus (GEO) database. Then, through the utilization of weighted gene co-expression network analysis (WGCNA), we identified 3 significant gene modules and ascertained 7 shared co-expressed genes affected by these models. Subsequently, through the utilization of differential gene expression analysis and protein-protein interaction network analysis for the 3 gene modules, the shared bottleneck gene Slc7a11 was identified. Moreover, the 7 shared co-expressed genes subjected to these three ALI models were used to identify shared ferroptosis-associated genes via the FerrDb database. Finally, the key gene Slc7a11 was confirmed and validated. In addition, we observed that Slc7a11 is both a driver and a suppressor gene in the FerrDb database. Interestingly, we found the expression level of Slc7a11 was significantly upregulated in the three ALI models. Experimentally, we confirmed the expression of Slc7a11 in rat ALI tissues by using immunofluorescence staining and real-time polymerase chain reaction (qRT-PCR) assays. Collectively, our findings complement the exploration of the shared pathogenesis of ALI. There are genetic features shared by ALI of different etiology and the increased expression of Slc7a11 was identified in the three different etiologies of ALI, which can improve our understanding of the shared molecular mechanisms underlying ALI.